THE EFFECTIVENESS OF USING GRAMMARLY ON HIGH SCHOOL STUDENTS' WRITING QUALITY - Khairum Nisa Jelita; Afrianto Daud; Masyhur Masyhur (International Journal of Educational Best Practices, 2023)
Grammarly has got a lot of attention among academics especially because it is a powerful tool that can be used by writers to improve their writing quality. They need it as a medium for correcting writing errors. This study aims to examine the effectiveness of using Grammarly on the students' writing quality of the eleventh-grade students at SMA Negeri 1 Ujung Batu. In particular, this study explores if there is any significant effect of Grammarly on students' writing quality in terms of grammatical accuracy, capitalization, spelling, and punctuation. This is quantitative research using the pre-experimental method. The subject consists of 30 students selected using a purposive sampling technique. The data were collected from a pre-test and a post-test of writing an explanation text written before and after being corrected using Grammarly. The hypothesis test was conducted using Wilcoxon Test. The result shows an alternative hypothesis which is the Asymp. Sig. is 0.00<0.05. So, Grammarly has a significant effect on students' writing quality in eleventh grade at SMA Negeri 1 Ujung Batu. This study implies that Grammarly can be useful as a learning media as self-editing for students to improve their writing ability.